MR of childhood-onset dentatorubral-pallidoluysian atrophy. - Miyazaki, M; Kato, T; Hashimoto, T; Harada, M; Kondo, I; Kuroda, Y (American Journal of Neuroradiology, 1995)
MR findings in a 14-year-old boy with progressive myoclonic epilepsy, who was diagnosed as having dentatorubral-pallidoluysian atrophy by DNA analysis, were compared with those of his father, who had adult-onset dentatorubral-pallidoluysian atrophy. Besides showing severe brain atrophy, especially of the brain stem tegmentum and cerebellum, MR showed diffuse periventricular hyperintensity on T2-weighted images. As compared with the proband, the father had a mild case.